Inter-parental conflict and academic achievement among adolescents of high schools in Bandar Abbas, Iran - Pour, Marjan Karimi; Mansor, Norwati; Mohd Kosni, Azlina (Kulliyyah of Education, International Islamic Education Malaysia, 2016)
This research was conducted with two objectives, to identify level of inter-parental conflict problems face by high school students in Bandar Abbas, and to investigate the relationship between level of inter-parental conflict and academic achievements among high schools students in Bandar Abbas. Participants consisted of 248 adolescent aged 17-18 who study in 3rd level and pre-university. A 27 items questionnaires was employed to measure inter-parental-conflict (including four dimensions parent-parent conflict, mother-child conflict, father-child conflict, problems in school). CGPA was used to measure academic achievement. The data were examined quantitative using, one sample t-test, and Spearman correlation. Results indicated that students of high schools in Bandar Abbas were faced by high level of inter-parental conflict, and a significant negative relationship between academic achievement and all dimensions of inter-parental conflict dimension.